Longitudinal Associations Between PTSD Symptoms and Dyadic Conflict Communication Following a Severe Motor Vehicle Accident. Issue 2 (March 2017) - Fredman, Steffany J.; Beck, J. Gayle; Shnaider, Philippe; Le, Yunying; Pukay-Martin, Nicole D.; Pentel, Kimberly Z.; Monson, Candice M.; Simon, Naomi M.; Marques, Luana
Abstract: There are well-documented associations between posttraumatic stress disorder (PTSD) symptoms and intimate relationship impairments, including dysfunctional communication at times of relationship conflict. To date, the extant research on the associations between PTSD symptom severity and conflict communication has been cross-sectional and focused on military and veteran couples. No published work has evaluated the extent to which PTSD symptom severity and communication at times of relationship conflict influence each other over time or in civilian samples. The current study examined the prospective bidirectional associations between PTSD symptom severity and dyadic conflict communication in a sample of 114 severe motor vehicle accident (MVA) survivors in a committed intimate relationship at the time of the accident. PTSD symptom severity and dyadic conflict communication were assessed at 4 and 16 weeks post-MVA, and prospective associations were examined using path analysis. Total PTSD symptom severity at 4 weeks prospectively predicted greater dysfunctional communication at 16 weeks post-MVA but not vice versa. Examination at the level of PTSD symptom clusters revealed that effortful avoidance at 4 weeks prospectively predicted greater dysfunctional communication at 16 weeks, whereas dysfunctional communication 4 weeks after the MVA predicted more severe emotional numbing at 16 weeks. Findings highlight the role of PTSD symptoms in contributing to dysfunctional communication and the importance of considering PTSD symptom clusters separately when investigating the dynamic interplay between PTSD symptoms and relationship functioning over time, particularly during the early posttrauma period. Clinical implications for the prevention of chronic PTSD and associated relationship problems are discussed. Highlights: Longitudinal paths between PTSD symptoms and couple communication were tested. Participants were recent survivors of severe motor vehicle accidents. Total PTSD symptoms predicted greater dysfunctional communication. Avoidance symptoms predicted greater dysfunctional communication. Dysfunctional communication predicted greater emotional numbing severity.